THE INFLUENCE OF FINANCIAL LITERACY, INVESTMENT KNOWLEDGE AND INVESTMENT MOTIVATION ON STUDENT INVESTMENT INTEREST IN LHOKSEUMAWE CITY - Sumi Amelya Harahap; Rico Nur Ilham; Ristati; Muttaqien (Universitas Efarina, 2023)
This study aims to determine whether financial literacy, investment knowledge and investment motivation affect student investment interest in Lhokseumawe City. The data used in this study are primary data where the data is obtained by distributing questionnaires to students in Lhokseumawe City. The sampling technique used is purposive sampling with non probability sampling method. The number of respondents used as samples in this study was 100 people using the Lameshow formula. The data were analyzed using the partial least square method using SmartPLS 4.0 software. The results of this study indicate that financial literacy has a positive and significant effect on student investment interest in Lhokseumawe City with an original sample value of 0.474 and a P value of 0.000, investment knowledge has a positive but insignificant effect on student investment interest in Lhokseumawe City with an original sample value of 0.165 and a P value of 0.111 and investment motivation has a positive and significant effect on student investment interest in Lhokseumawe City with an original sample value of 0.334 and a P value of 0.001. This shows that financial literacy and investment motivation are very important for every student in Lhokseumawe City to increase their investment interest. Meanwhile, investment knowledge, high or low, has no effect on student investment interest in Lhokseumawe City.